The Significance of the Role of Physical Culture in Modern Conditions in Work with Student Youth (On the Example of KSU Named After Berdakh) - Tudimuratov Jengis Auezovich (Periodica Journal, 2022)
This article examines the degree of influence of physical culture on the life of students. The main tasks of the discipline "Physical Culture" are shown, as well as the features and specifics of the subject are listed.
Keywords: physical culture; health; individual; personality